Spin-transfer pulse switching: From the dynamic to the thermally activated regime - Bedau, D.; Liu, H.; Sun, J. Z.; Katine, J. A.; Fullerton, E. E.; Mangin, S.; Kent, A. D. (Applied physics letters, 2010)
The effect of thermal fluctuations on spin-transfer switching has been studied for a broad range of time scales (subnanoseconds to seconds) in a model system, a uniaxial thin film nanomagnet. The nanomagnet is incorporated into a spin-valve nanopillar, which is subject to spin-polarized current pulses of variable amplitude and duration. Two physical regimes are clearly distinguished: a long pulse duration regime, in which reversal occurs by spin-transfer assisted thermal activation over an energy barrier, and a short-time large pulse amplitude regime, in which the switching probability is determined by the spin-angular momentum in the current pulse.